1 Transfer of military surgical simulation developments to the civilian sphere. Issue 2 (23rd March 2023) - Cohen, HML; Swain, CS; Stannard, A; Faulconer, ER; Parker, P; Hand, CJ; Pallister, I
Abstract : Introduction: Defence Medical Services has a history of sharing clinical practice and innovation with the civilian sector. Changes to surgical training has meant acquiring and maintaining trauma surgical skills is becoming more difficult. Anatomically correct, bleeding junctional vascular trauma task trainers have been developed for the Military Operational Specialist Team Training (MOSTT) course. We investigated the benefit of these models on a civilian trauma course attended by non-vascular surgeons. The Mass Casualty Damage Control Surgery Ortho Trauma Surgery (DCS) Course is taught by a combined civilian and military faculty. Method: Groin, pelvic and shoulder haemorrhage surgical task trainers with pulsatile blood flow were used in the course to simulate junctional haemorrhage requiring surgical intervention. Participants completed modified pre and post course questionnaires to record changes in their self-reported confidence. Results: Ten participants completed simulation scenarios using the models and provided feedback. Approach to femoral artery, subclavian artery, gaining proximal and distal arterial control and temporary arterial shunting all had statistically significant improvements in participant confidence (p<0.0047, p<0.0017, p<0.0012 and p<0.0009). Conclusion: These findings mirror the experience on the MOSTT course where 63% of participants indicated that their confidence had improved. These results demonstrate the value for high fidelity surgical simulation in civilian practice to help maintain currency in less frequently encountered injury patterns. The training includes the whole team in high fidelity DCS simulation without the need for live tissue or cadaveric material and shows that surgical mannequins developed for the military environment have utility on civilian trauma courses. Research by the authors about the effects of this model on surgical ability and performance is ongoing.